Transformation of Conventional Bus Terminal Management Towards Smart Mobility in Manado City - Fajria Hanifah Agustina; Helen Dian Fridayani; Achmad Nurmandi (Spirit Publik: Jurnal Administrasi Publik, 2026)
The purpose of this study is to evaluate how the Manado City Government supports Smart Mobility by managing and optimizing bus terminals. In contrast to the low use of public transportation, the prevalence of private vehicles, which reached 503,323 units in 2023, and the high levels of urban mobility serve as the driving forces behind this study. Using secondary data from Manado City Government policy documents, Transportation Agency reports, transportation statistics, scientific journals, and credible media outlets, a qualitative literature review was conducted. The Miles and Huberman interactive model was used to analyze the data through the stages of data reduction, presentation, and conclusion drawing. Source triangulation was used to validate the results. The results show that Manado City's bus terminal management remains traditional, with Terminal Paal 2's distribution restricted and supporting infrastructure insufficient. According to the Importance-Performance Analysis method, public transport user satisfaction has a negative gap value of -1.60, meaning that service quality is significantly below user expectations. Additionally, there is still little or no systemic integration of Smart Mobility indicators, such as public transportation, clean energy transportation, and real-time information access. To improve terminal efficiency as intelligent and sustainable urban mobility nodes, these findings highlight the need to reform urban transportation policies by integrating digital technologies and creating real-time information systems.